Pengaruh Advertising Awareness, Brand Image dan Brand Awareness terhadap Keputusan Pembelian - Nakane Dellia Kheny Muliawan; Nina Nurhasanah (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
The development of technologyandsocial media encouragescompanies to leveragedigital strategies in building their brands. Advertising awareness is one of the key factors in enhancing brand awareness and brand image, which ultimately influences consumer behavior. This study aims to analyze the influence of advertising awareness, brand image, and brand awareness on consumer purchasing decisions on local brand clothing products Colorbox which carries a casual look style. In the context of increasingly competitive local fashion industry competition, building brand image and consumer awareness of advertising are the keys to increasing competitiveness. This study uses a quantitative approach with a survey method distributed to respondents aged 17 –40 years who have purchased Colorbox products in the last three months. The sampling technique used purposive sampling with a total of 105 respondents. Data were analyzed using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method. The results of the study show that advertising awareness has a significant effect on brand image and brand awareness. Brand awareness is also proven to have a positive influence on brand image, and brand image serves as a mediator in the relationship between advertising awareness and brand awareness. These findings highlight the importance of effective marketing communication in shaping positive brand perceptions and encouraging consumer purchasing decisions.